Alegal : Biopolitics and the Unintelligibility of Okinawan Life. - Shimabuku, Annmaria M. (New York : Fordham University Press, 2018)
Alegal traces the trans-Pacific biopolitics between a postwar American empire of military bases and postcolonial Japan that secured Okinawa as a U.S. military fortress. It shows how both managed sex in its base towns from 1945 to 2015, and elucidates the potential for Okinawan insurgency in response to this collaboration.
Cover -- ALEGAL -- Title -- Copyright -- Dedication -- CONTENTS -- Preface -- Note on Translations and Romanizations -- List of Commonly Used Acronyms and Abbreviations -- Introduction -- 1. Japan in the 1950s: Symbolic Victims -- 2. Okinawa, 1945-1952: Allegories of Becoming -- 3. Okinawa, 1952-1958: Solidarity under the Cover of Darkness -- 4. Okinawa, 1958-1972: The Subaltern Speaks -- 5. Okinawa, 1972-1995: Life That Matters -- Conclusion -- Acknowledgments -- Notes -- Selected Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Miscegenation-Japan-Okinawa-shi-History-20th century; Military bases, American-Social aspects-Japan-Okinawa-ken.; Soldiers-Sexual behavior-United States-History-20th century; Biopolitics-Japan-Okinawa-shi.; Okinawa-shi (Japan)-History-20th century; Electronic books